Elaboration of photoactive tio particles by CVD : effect of operational parameters / Ayumi Mameda ... [et al.] - Mameda, Ayumi; Shioi, Masahiko; Sakai, Yuka; Ito, Takuya; Kato, Shigeru; Yamasaki, Akihiro; Suzuki, Seiichi; Kojima, Toshinori (Universiti Teknologi MARA, Pulau Pinang, 2015)
The TiO2 photocatalyst is used for various purposes such as a cleanup of polluted air, antifouling, sterilization, deodorization, and so on. The purpose of this study is to synthesize the TiO2 photocatalyst fines in the gas phase. We used TTIP (titanium tetraisopropoxide) as the precursor because gas phase processes using chlorine compounds cause serious operational problems such as corrosion. As TTIP has close boiling and thermal decomposition temperatures, liquid TTIP was directly (without vaporization) introduced through a water-cooled tube, while, H2O vaporized in a separate vaporizer was introduced from the lower part of the reactor. At the reactor temperature of 1000oC, the more Ar flow rate at the TTIP side increased without changing the flow rate of TTIP keeping the total flow rates of TTIP side and H2O side almost similar, the smaller particle size of TiO2 was elaborated, the less the carbon content became, and the higher photocatalytic activity was observed. Then, the effect of reactor temperature between 800oC and 1100oC was examined under the optimum condition of flow rate. At the reactor temperature of 1000oC, small particle size of TiO2 with the highest anatase content was elaborated, which showed the highest photocatalytic activity.